All‐optically induced ultrafast currents: Beyond the continuous‐wave limit. Issue 9 (7th June 2013) - Priyadarshi, Shekhar; Pierz, Klaus; Bieler, Mark; Ulrich, Sven M.; Jetter, Michael; Michler, Peter
Abstract We observe a new type of optically induced linear‐photogalvanic current in GaAs quantum wells which only exists if the linear polarization of the excitation pulse slowly rotates versus time and if the response of the coherent polarization is non‐instantaneous. The current vanishes in the continuous‐wave limit. Microscopically, it results from a phase mismatch of two orthogonal transition dipole moments. Macroscopically, the current can be linked to an antisymmetric tensor element and, thus, it is different than previously known linear‐photogalvanic currents which are linked to symmetric tensor elements. Our observations of asymmetric response tensors provide the possibility for simultaneous coherent control of commutative and anti‐commutative operations with respect to two time‐delayed pulses. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)